The effect of bone marrow mesenchymal stem cells on recovery of skeletal muscle after neurotization surgery in rat - Farjah, Gholam Hossein (Iran J Basic Med Sci, 2018)
OBJECTIVE(S): When the nerve is injured near its entrance to the muscle belly, we cannot perform conventional methods. One useful method in such a situation is neurotization surgery. In this study, Bone marrow mesenchymal stem cells (BMSCs) implanted into the paralyzed muscle after neurotization surgery. These cells can stimulate axon growth and motor endplate formation, also prevent muscle atrophy. MATERIALS AND METHODS: Thirty-six adult male Sprague-Dawley rats were randomized into six groups: intact group, sham surgery group, control group, DMEM group, cell+DMEM group, denervated group. The motor nerve of the lateral head of gastrocnemius muscle was cut, and the proximal portion of the severed nerve was transplanted to the proximal third of the muscle paralysis. BMSCs with/or DMEM was injected into the site of injury. All animals were evaluated by withdrawal reflex latency (WRL), electromyography, muscle weight, histology and immunohistochemistry. RESULTS: The WRL difference between the control and cell+DMEM groups at weeks 4 and 12 post-operation was statistically significant (P<0.05). The mean number of motor end plates in cell+DMEM group was more than control group (P<0.05). At 12 weeks post-operation, the difference of the mean nerve conduction velocity (NCV) between cell treated group and sham surgery groups were not statistically significant (P>0.05). In weeks 4 and 12 post-operation, the mean fiber diameters in cell+DMEM group were more than control group (P<0.05). CONCLUSION: The results of this study demonstrate that transplantation of BMSCs after neurotization surgery, prevent muscle atrophy and improve muscle function.